HEGEMONI DALAM PONDOK PESANTREN DAN KAITANNYA DENGAN PELECEHAN SEKSUAL PADA SANTRIWATI - Fitri Karua Lukman Murad, Fitri Karua Lukman Murad; Abdul Firman Ashaf, Abdul Firman Ashaf; Tina Kartina, Tina Kartina (Institut Agama Islam Negeri Ponorogo, 2024)
This research aims to analyze the hegemony that occurs in the Islamic boarding school environment and whether it is related to the rise of sexual violence against female students. Power domination of kiai, patrilineal culture, and the rules of sami'na wa ato'na seemed to kill the right of the students to grow critical and only have to follow the orders of the kiai. The latest phenomenon, kiai’s power domination being the opportunity for rampant sexual violence to occur within the scope of special girls' pesantren education. The method used is literature study, which is tracing writing sources that have been made before. In other words, the term literature study is also very familiar with the term literature study. The purpose of this study is to determine the pattern of hegemonic communication by kiai y as the leader of pesantren towards the girl students.